CHARACTERIZATION OF PATIENTS WITH OBSESSIVE-COMPULSIVE DISORDER: AN EPIDEMIOLOGICAL STUDY - Adriana Gonçalves Oliveira; Juliana Ferreira Silva; Laura Campos Teles; Richardson Miranda Machado (Universidade Federal do Paraná, 2012)
This is a retrospective, exploratory study, undertaken in a psychiatric institution with the aim of characterizing the patients affected by Obsessive-Compulsive Disorder by sex, age, provenance, duration of hospitalization, type of discharge, type of hospitalization, and source of financing of hospitalization. The sample comprised 61 patients, the majority of whom were female (47-77%), age range over 41 years old (41-67%), who came to hospital from the family home (31-50.8%) and length of hospitalization of 30 days (33-54.1%). The most frequent type of discharge was medical (51-83.6%), and there were similar prevalences for first hospitalizations (30-49.2%) and re-hospitalizations (31-50.8%); the main financer for hospitalization was the Unified Health System (54-88.5%). Actions for the early diagnosis of this disorder must be developed so that the treatment may be initiated promptly, so as to avoid the worsening of obsessions and compulsions